(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article is devoted to the issues of financial support for public-private partnership in the field of preschool education. In the context of limited budget resources and increasing demands on the quality of educational services, public-private partnership is an effective tool for combining the efforts of the state and the private sector. The main problems are considered, such as insufficient interest of business, shortcomings in the regulatory framework and information opacity. Recommendations are proposed for improving the financial models of PPPs to increase their efficiency and attractiveness.